2016
DOI: 10.3389/fimmu.2016.00181
|View full text |Cite
|
Sign up to set email alerts
|

Host Intracellular Signaling Events and Pro-inflammatory Cytokine Production in African Trypanosomiasis

Abstract: Pathogens, such as bacteria, viruses, and parasites, possess specific molecules or proteins that are recognized by several host innate immune receptors, leading to the activation of several intracellular signaling molecules and pathways. The magnitude and quality of these events significantly affect the outcome of infection. African trypanosomes, including Trypanosoma congolense, are capable of manipulating the host immune response, including the activity of macrophages, which are the key immune cells that con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 93 publications
0
13
0
Order By: Relevance
“…The induction of type 2 macrophages is a prominent feature of the immunosuppression that occurs during chronic T. brucei infections. Studies have shown that trypanosomes trigger a switch in macrophage activation from pro-inflammatory (or classically-activated) cells to a more anti-inflammatory (or alternatively activated) state (74, 104,110,136,137). This switch in macrophage character skews the host immune response from Th1 to Th2, resulting in an anti-inflammatory environment that promotes parasite survival in the host (138).…”
Section: Macrophages-the Big Playersmentioning
confidence: 99%
“…The induction of type 2 macrophages is a prominent feature of the immunosuppression that occurs during chronic T. brucei infections. Studies have shown that trypanosomes trigger a switch in macrophage activation from pro-inflammatory (or classically-activated) cells to a more anti-inflammatory (or alternatively activated) state (74, 104,110,136,137). This switch in macrophage character skews the host immune response from Th1 to Th2, resulting in an anti-inflammatory environment that promotes parasite survival in the host (138).…”
Section: Macrophages-the Big Playersmentioning
confidence: 99%
“…In addition, an estimated three million cattle die from this disease each year, resulting in economic loss of four billion US dollars in Africa ( 5 ). Following malaria and schistosomiasis, African trypanosomiasis is the third significant contributor to the global burden of parasitic diseases ( 6 ). The causative agents of this disease are various species of protozoan parasites belonging to genus of Trypanosoma .…”
Section: Introductionmentioning
confidence: 99%
“…The causative agents of this disease are various species of protozoan parasites belonging to genus of Trypanosoma . Among them, Trypanosoma brucei rhodesiense and Trypanosoma brucei gambiense infect humans, while Trypanosoma brucei brucei, Trypanosoma congolense , and Trypanosoma vivax are the major species causing animal infections ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…The hallmark of initial inflammation is increased vascular permeability, blood flow, and leukocytosis at the injured tissue site [3]. During an inflammatory response, intracellular signal events, driven by pro-inflammatory mediators and cytokines, are activated [4]. Among immune cells, macrophages play a major role in the inflammatory responses through the production of various mediators such as nitric oxide (NO), prostaglandin E 2 (PGE 2 ), and pro-inflammatory cytokines [5].…”
Section: Introductionmentioning
confidence: 99%